The achene mucilage hydrated in desert dew assists seed cells in maintaining DNA integrity: adaptive strategy of desert plant Artemisia sphaerocephala. - Xuejun Yang (Public Library of Science (PLoS), 2011)
Despite proposed ecological importance of mucilage in seed dispersal, germination and seedling establishment, little is known about the role of mucilage in seed pre-germination processes. Here we investigated the role of mucilage in assisting achene cells to repair DNA damage during dew deposition in the desert. Artemisia sphaerocephala achenes were first treated γ-irradiation to induce DNA damage, and then they were repaired in situ in the desert dew. Dew deposition duration can be as long as 421 min in early mornings. Intact achenes absorbed more water than demucilaged achenes during dew deposition and also carried water for longer time following sunrise. After 4-d dew treatment, DNA damage of irradiated intact and demucilaged achenes was reduced to 24.38% and 46.84%, respectively. The irradiated intact achenes exhibited much higher DNA repair ratio than irradiated demucilaged achenes. Irradiated intact achenes showed an improved germination and decreased nonviable achenes after dew treatment, and significant differences in viability between the two types of achenes were detected after 1020 min of dew treatment. Achene mucilage presumably plays an ecologically important role in the life cycle of A. sphaerocephala by aiding DNA repair of achene cells in genomic-stressful habitats.